2014
DOI: 10.1007/s12263-014-0384-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of melanocortin 4 receptor gene variation with satiation and gastric emptying in overweight and obese adults

Abstract: Melanocortin 4 receptor (MC4R) has a major role in energy homeostasis. The rs17782313 polymorphism, mapped 188 kb downstream from MC4R, has been associated with satiety, higher body mass index (BMI) and total calorie intake in adults. To assess the association of rs17782313 with gastric functions, satiation, or satiety, we studied 178 predominantly Caucasian overweight and obese people: 120 females, 58 males; mean BMI 33.4 ± 5.3 kg/m 2 (SD); age 37.7 ± 11.2 years. Quantitative traits assessed were gastric empt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
(60 reference statements)
1
15
0
1
Order By: Relevance
“…Genes that have been associated with type 2 diabetes or obesity in epidemiological studies have been preliminarily shown to alter gastric motor functions, satiation, or satiety (24,29,30). Previously, other UCP-3 gene variants have been associated with obesity or abdominal obesity (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes that have been associated with type 2 diabetes or obesity in epidemiological studies have been preliminarily shown to alter gastric motor functions, satiation, or satiety (24,29,30). Previously, other UCP-3 gene variants have been associated with obesity or abdominal obesity (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…A sample size assessment for detecting clinically relevant associations for each genotype was examined by estimating the differences between two groups (i.e., assuming a dominant genetic model) that could be detected given the observed variation in the measured responses and the number of subjects that were anticipated in each genotype group, based on our prior studies that estimated the minor allele frequency in the same community . The differences between genotype groups that could be detected with approximately 80% power (two‐sided α level of 0.05) using a two‐sample t ‐test [assuming the listed pooled standard deviation (SD)] are shown in Appendix Table . The table illustrates the effect sizes demonstrable based on different sizes of groups for each genotype; this is necessary because the minor allele frequencies vary for the different genotypes studied (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we invited for this study 58 individuals with obesity (BMI 30–40 kg/m 2 ) and known accelerated gastric emptying (GE) of solids (GE T 1/2 < 79 min or GE 1 h >35%) who had participated in recent studies (Acosta et al. 2014b, ,b). We selected for randomization in this study the first 20 subjects who agreed to participate.…”
Section: Methodsmentioning
confidence: 99%
“…These variants were also associated with increased waist size [8], body mass index (BMI), and insulin resistance [7,9]. Moreover, rs17782313 was associated with postprandial satiation symptoms and slower gastric emptying [10].…”
Section: Introductionmentioning
confidence: 99%